Thinking Culture and Cultural Studies-from/of the Global South - Shome, Raka (Communication and critical/cultural studies, 2019)
This essay invites us to consider the need to rethink culture and some theoretical/intellectual assumptions in Cultural Studies when we bring up the issue of the "Global South." The essay makes a case for "going South" in Cultural Studies. It advances a notion of the South that is based on a frame of dispossession. The first section offers a historical overview of the Global South and considers where the Global South is today. The second section attempts to rethink the notion of 'culture' and some intellectual orientations in Cultural Studies when we move to the Global South.